A Model for Digitization Success in Ugandan TVETs: Evaluation Through Structured Walkthroughs and Simulation - Muinda, Patrick Emmanuel; Basaza-Ejiri, Annabella Habinka; Maiga, Gilbert; Mayoka, Kituyi (Journal of Information System and Informatics, 2025)
This study proposes an information systems model to enhance the success of digitization projects in Ugandan Technical and Vocational Education and Training (TVET) institutions. The research was based on agency theory, with additional insights drawn from the DeLone and McLean Information Systems Success Model and the Dynamic Capabilities Framework. The model was developed based on key constructs such as Communication, Task Programmability, Goal Conflict, Shirking, and Process Quality. To evaluate its effectiveness, a structured walkthrough was conducted using a prototype simulator (SimPro), where expert evaluators assessed its usability, completeness, and performance. Results indicate that 96% of experts rated the model as highly usable, while 92% agreed that it accurately represents key digitization principles. The model’s usability significantly influenced expert recommendations for adoption (Spearman’s rho = 0.457, p = 0.001). Based on expert feedback, refinements were made to enhance stakeholder engagement, accountability tracking, and task efficiency. These findings suggest that the model has strong potential to improve digitization success rates by enhancing stakeholder engagement, accountability tracking, and task efficiency. Expert evaluators confirmed that these factors are critical to successful digitization in TVETs, indicating that structured implementation of this model could lead to more effective digitization outcomes. However, further empirical validation through real-world implementation is recommended to measure long-term impact.